Integrating Adaptive Testing into Flipped Mathematics Classrooms: Effects on Prospective Teachers' Critical Thinking and Reasoning Quality - Arif Abdul Haqq; Nurma Izzati; Onwardono Rit Riyanto; Dionisio Aquino Alves; Siti Rahmah (MASI Mandiri Edukasi, 2026)
This study addresses the limited development of students’ mathematical critical thinking ability in conventional classrooms and investigates the effectiveness of a flipped classroom supported by adaptive testing. The objective of this study is to examine the effect of this instructional approach on students’ mathematical critical thinking ability. An explanatory sequential mixed-methods design with a quasi-experimental pretest–posttest control group structure was employed, involving 64 students assigned to experimental and control groups. Data were collected through pre- and posttests, interviews, and classroom observations. Quantitative analysis using an independent samples t-test revealed a statistically significant difference in posttest scores, t(62) = 4.28, p < .001, with a large effect size (Cohen’s d = 1.07). The experimental group achieved a medium normalized gain (0.47), while the control group demonstrated a low gain (0.18). Qualitative findings indicated that students in the experimental group demonstrated more elaborated argument clarification, systematic process evaluation, relational inference and deduction, and strategic completion of missing information. In contrast, control group responses were predominantly procedural and recall-oriented. These findings suggest that the integration of flipped pedagogy and adaptive testing enhances higher-order reasoning processes and students’ mathematical performance, while adaptive testing is theoretically associated with more calibrated cognitive challenge and potentially more precise ability estimation.